Focal Neurologic Deficits with Hypoglycemia - J Gordon Millichap (Pediatric Neurology Briefs)
Clinical manifestations and outcome of transient focal neurologic deficits (TFND) associated with hypoglycemia were evaluated in 44 children with insulin-dependent diabetes mellitus observed retrospectively during a 5 year period at the University of Trieste, Italy.